Fluorinated chiral nematic liquid crystal dimers based on (S)-1-phenylethane-1, 2-diol. Issue 5 (8th April 2020) - Zang, Xiang-Yu; Gao, Li; Zhang, Rui; Dong, Liang; Chen, Xin-Shi; Li, Yu-Nong; Yao, Dan-Shu; Hu, Jian-She; Jia, Ying-Gang; Li, Feng-Hong; Tian, Mei
ABSTRACT: A series of symmetric liquid crystal (LC) dimers with the same chiral core (S)-1-phenylethane-1, 2-diol ((S)-PE ) have been synthesised, termed TBDA-(S)-PE, 3F3B-(S)-PE, 3F2B-(S)-PE, 1F3B-(S)-PE, 1F2B-(S)-PE, respectively. Chemical structures and LC properties of the five symmetric LC dimers were characterised by Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance hydrogen spectrometer ( 1 H NMR), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), X-ray diffraction (XRD) and polarised optical microscopy (POM). TBDA-(S)-PE displayed enantiotropic chiral smectic A (Sm A*) phase while 3F3B-(S)-PE, 3F2B-(S)-PE, 1F2B-(S)-PE all displayed enantiotropic chiral nematic (N*) phase and 1F3B-(S)-PE displayed monotropic N* phase. The results indicated that the removal of the flexible spacers between the rigid mesogenic arm and the chiral core facilitated the formation of the N* phase. When the rigid mesogenic units are connected to the chiral core directly, the structure of the terminal fluorine group and the rigidity of the mesogenic unit played certain influence on the thermal properties of the LC dimers, but did not change the type of mesomorphic phase. Compared to 3F3B-(S)-PE and 1F3B-(S)-PE, 3F2B-(S)-PE and 1F2B-(S)-PE displayed wider LC ranges, respectively, suggesting molecular regularity had greater influence on LC-isotropic (I) transition temperature. Abstract :